2011
DOI: 10.1016/j.ejogrb.2011.07.035
|View full text |Cite
|
Sign up to set email alerts
|

External validation of the adapted Risk of Malignancy Index incorporating tumor size in the preoperative evaluation of adnexal masses

Abstract: Both RMI-3 and RMI-4 were able to discriminate between non-invasive lesions and invasive malignant adnexal masses, with similar performances. Including tumor size in the RMI does not improve its performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…The performance of RMI-3 and RMI-4 reported in this study was in agreement with many previous studies (8,24). Both RMI-3 and RMI-4 are accurate in predicting malignant ovarian masses than in borderline cases.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The performance of RMI-3 and RMI-4 reported in this study was in agreement with many previous studies (8,24). Both RMI-3 and RMI-4 are accurate in predicting malignant ovarian masses than in borderline cases.…”
Section: Discussionsupporting
confidence: 92%
“…This study has addressed the performances of RMI-3 at a cut-off value of 200 and RMI-4 at cut-off value of 450 in preoperative evaluation of adenxal masses. At these cut-off levels, RMI-3 (9-11) and RMI-4 (8,21,24) reported the best performance in previous studies.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Most previous studies confirm this finding, as in the 2011 study by Petronella et al, which found that tumor size was useless for diagnosis of malignant ovarian masses because 60% of benign cases had the tumor size greater than 7 cm. 16 Although serum CA-125 level was high in 85.7% of malignant cases, 20.8% of benign cases also had CA-125 levels above the allowable cut-off level 35 U/mL. Furthermore, high CA-125 levels are known to be indicative of other gynecological conditions such as endometriosis and pelvic infections.…”
Section: Discussionmentioning
confidence: 99%